Kinect for interactive AR anatomy learning - Meng, Ma; Fallavollita, Pascal; Blum, Tobias; Eck, Ulrich; Sandor, Christian; Weidert, Simon; Waschke, Jens; Navab, Nassir (2013 IEEE International Symposium on Mixed and Augmented Reality, ISMAR 2013, 2013)
Education of anatomy is a challenging but crucial element in educating medical professionals, but also for general education of pupils. Our research group has previously developed a prototype of an Augmented Reality (AR) magic mirror which allows intuitive visualization of realistic anatomical information on the user. However, the current overlay is imprecise as the magic mirror depends on the skeleton output from Kinect. These imprecisions affect the quality of education and learning. Hence, together with clinicians we have defined bone landmarks which users can touch easily on their body while standing in front of the sensor. We demonstrate that these landmarks allow the proper deformation of medical data within the magic mirror and onto the human body, resulting in a more precise augmentation. © 2013 IEEE.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Anatomy Learning; Augmented Reality; Kinect